Acculturation of International Doctoral Students: Perspectives from Students, Staff, and the Institution - Gao, Bing (Journal of International Students, 2026)
This qualitative case study examines international doctoral students’ acculturation from the perspectives of students, a Midwestern U.S. university, and university staff. Fourteen students completed a survey and participated in two rounds of interviews. Using social categories and the experiential domain in Núñez’s (2014) multilevel model of intersectionality, students, grouped by acculturation strategies and cultural background, described distinct acculturative stressors and coping strategies. Additionally, five university staff members were interviewed about perceptions of international doctoral students’ acculturation and the services they provided. Observations of two orientation sessions organized by the University were also conducted. Data were analyzed through the organizational, intersubjective, and experiential domains of Núñez’s (2014) model and revealed effective support and structural gaps in services provided by staff and the University, which remain underexplored in prior research. This study adapts Núñez’s (2014) model and offers implications for researchers and educators to provide tailored and responsive support for international students.